Reassessment of Pioglitazone for Alzheimer’s Disease - Saunders, Ann M.; Burns, Daniel K.; Gottschalk, William Kirby (Frontiers in Neuroscience, 2021)
Alzheimer’s disease is a quintessential ‘unmet medical need’, accounting for 65% of progressive cognitive impairment among the elderly, and 700,000 deaths in the US in 2020. In 2019, the cost of caring for Alzheimer’s sufferers was 244B, not including the emotional and physical toll on caregivers. In spite of this dismal reality, no treatments are available that reduce the risk of developing AD or that offer prolonged mitiagation of its most devestating symptoms. This review summarizes key aspects of the biology and genetics of Alzheimer’s disease, and we describe how pioglitazone improves many of the patholophysiological determinants of AD. We summarize the results of pre-clinical experiments, clinical trials and longitudinal observational studies that demonstrate it is a time- and dose-dependent protective factor, and we propose that additional large-scale clinical trials are required to validate these conclusions and identify treatment regimens that will maximize its benefits